A survey of staffing levels in paediatric diabetes services throughout the UK. Issue 2 (8th December 2017) - Charalampopoulos, D.; Amin, R.; Warner, J. T.; Viner, R. M.; Campbell, F.; Edge, J. A.; Stephenson, T.
Abstract: Aims: To assess staffing levels of healthcare professionals involved in the care of children and young people with diabetes in the UK. Methods: A web‐based questionnaire was distributed to lead consultant paediatricians from all paediatric diabetes services in the UK between October and December 2014. Data on staffing levels and other aspects of diabetes services were collected and differences between the four nations of the UK and across the 10 English diabetes networks were explored. Results: Some 175 services (93%) caring for 29 711 children and young people aged ≤ 24 years with diabetes participated in the survey. Northern Ireland and Wales had the lowest ratio of total staff to patient population. Nursing caseloads per one whole‐time equivalent (WTE) nurse ranged from 71 patients in England to 110 patients in Northern Ireland with only 52% of the UK services meeting the Royal College of Nursing recommended nurse‐to‐patient ratio of > 1 : 70. Scotland and Northern Ireland had the highest ratio of consultants and fully trained doctors per 1000 patients (3.5 WTE). Overall, 17% of consultants had a Certificate of Completion of Training in Endocrinology and Diabetes. Some 44% of dietitians were able to adjust insulin dose. Only 43% of services provided 24‐h access to advice from the diabetes team and 82% of services had access to a psychologist. Staffing levels adjusted for volume were not directly related to glycaemic performance of services in England and Wales. Conclusions: Wide variations in staffing levels existed across the four nations of the UK and important gaps were present in key areas. What's new?: The rising prevalence of diabetes and the increased complexity of intensive insulin regimens pose new challenges to paediatric diabetes services and their workforce. The latest survey of UK paediatric diabetes services in 2008 highlighted important deficiencies in staffing levels across services, but the current state is unknown. We found wide variations in staffing levels of paediatric diabetes services across the UK, with heavy caseloads for psychologists and dietitians in Northern Ireland and Wales. Half of the services in the UK met the recommended staffing levels for nurses. We observed important gaps in 24‐h access to advice from the diabetes team.